A Strong Convergence Theorem for Total Asymptotically Pseudocontractive Mappings in Hilbert Spaces. (20th September 2012) - Ding, Chuan; Quan, Jing
Abstract : Demiclosedness principle for total asymptotically pseudocontractive mappings in Hilbert spaces is established. The strong convergence to a fixed point of total asymptotically pseudocontraction in Hilbert spaces is obtained based on demiclosedness principle, metric projective operator, and hybrid iterative method. The main results presented in this paper extend and improve the corresponding results of Zhou (2009), Qin, Cho, and Kang (2011) and of many other authors.